KEANEKARAGAMAN LICHENES (LUMUT KERAK) DI SEKITAR PERKEBUNAN TEH PTP NUSANTARA VI DANAU KEMBAR KECAMATAN GUNUNG TALANG KABUPATEN SOLOK - Jumaidi, Oki; Fifendy, Mades; M, Des (Pendidikan Biologi, 2013)
ABSTRACT Many people ascription that rural area of its environment of cleanness and free from pollution, opinion like that not yet of course can be made by reference for interpreting about situation of environment of rural. This matter earn us see from more and more him consumer of motor vehicle and industrial factories able to generate problems which serious enough so that can bother flora productivity residing in around factory area. This research aim to to know types of lichenes ( crust moss) got in Nagari Batang Barus District Of Gunung Talang Sub Province of Solok. This Research type is descriptive research by using method of survey. Gathering of sampel and Record Keeping of type of lichenes ( crust moss) conducted by direct field. Result of obtained research in Jorong Kayu Jao Kenagarian Batang Barus District Of Gunung Talang Sub Province of Solok in finding 32 crust moss species namely 11 species with morphology type of foliose, 8  species  with  morphology type of  fruticosa,  13  species  with  morphology type  of crustuse. Of conducted research hence concluded that air around plantation of tea of PTP Nusantara VI Danau Kembar and of Jorong Kayu Jao Kenagarian Batang Barus District Of Gunung Talang Sub Province of Solok still cleanness, because of to the number of types of lichenes ( crust moss) found.